PENGARUH HUBUNGAN PEMASARAN KEWIRAUSAHAAN, KECEPATAN INOVASI, DAN KEUNGGULAN POSISI UNTUK PENINGKATAN KINERJA PEMASARAN - Irfan Wildzan Muafa; Putri Inggrid Maria Risamasu (EKONOMI & SOSIAL, 2018)
The research this time aims to examine the effect of Entrepreneurship Marketing on the Marketing Performance of a food and beverage SME through the Speed of Innovation variable and also through the variable Excellence of the position of an SME. The research carried out 150 samples of food and beverage SMEs in Semarang , Central Java from a population of 1488 food and beverage SMEs. This study uses descriptive quantitative research methods. This study found that entrepreneurial marketing has a positive influence on the innovation speed and also has a positive influence on position advantage. And the superiority of the position advantage has a positive influence on marketing performance. So that it can be concluded that entrepreneurship marketing can affect marketing performance through variable speed of innovation and also position superiority